An ecopoetic inquiry into Emily Dickinson's dwelling earthward - Artukarslan, Ayşe Beyza. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis re-introduces Emily Dickinson as a nature poet and furthermore, an ecopoet through the examination of selected poems with an emphasis on the unique features applied by the poet from breaking down grammar rules to upsetting the conventional rhythmic ordinance of verse. The importance of Dickinson’s peculiar composition is underlined after the philosophical discussion of animal from antiquity to present day, from an ontological outcast to an ethical object and finally to an autonomous subject. Introduction of ecology to literature and in particular to poetry is analysed through ecocriticism. With a specific emphasis on the current environmental crisis and animal liberation movements, this thesis re-reads Dickinson’s poetry with the help of animal studies and ecopetic disciplinary approaches. By presenting Emily Dickinson’s dwelling earthward as an exemplary one and perhaps as a way of salvation of human and non human relations, the ultimate aim is to show the possibility to enhance the perception of nature in the eyes of human animal by carrying it from the circumference to the centre of attention.